Strategi manajemen dalam perbankan dan lembaga keuangan syariah: Pendekatan risiko, pemasaran, dan manajemen aset - Faizah, Nilna Alfa (Maliki Interdisciplinary Journal, 2025)
This article discusses various management strategies implemented in Islamic banking and other Islamic financial institutions, focusing on strategic risk management, information technology-based marketing, and asset and liability management. This study examines the growth dynamics of the Islamic banking industry in Indonesia, as well as the challenges and opportunities emerging in the current digital era. The analytical method used is a literature review of various recent academic journals that discuss strategic management perspectives in the context of Islamic finance. The results show that an integrated strategy of risk management, innovative marketing, and comprehensive asset management enhances the competitiveness and sustainability of Islamic financial institutions. In conclusion, the implementation of adaptive management strategies based on Islamic principles is crucial to support sustainable industry growth and meet the needs of the modern digital market.